The negative effects of exercise on the quality and quantity of sleep in athletes - Cofrancesco, C. J. (Academic Festival, 2018)
The purpose of this study was to review scientific literature to determine if exercise has a negative effect on the quality and quantity of sleep in athletes. Four scientific articles were used to review the effects of exercise on the quality and quantity of sleep. When high intensity exercise was introduced total sleep time and sleep efficiency decreased.